1996
DOI: 10.1002/jbmr.5650110514
|View full text |Cite
|
Sign up to set email alerts
|

Bone sialoprotein expression in primary human breast cancer is associated with bone metastases development

Abstract: Breast cancer metastasizes to bone more frequently than to any other organ, and over 80% of advanced breast cancer patients develop bone metastases. Our recent demonstration that human breast cancer cells express bone sialoprotein (BSP), a bone matrix protein, provides a possible clue for the selective affinity of breast cancer cells for bone. We tested the hypothesis that detection of BSP in primary human breast cancer could be a potential indicator of the ability of breast cancer cells to metastasize to bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 13 publications
1
39
0
3
Order By: Relevance
“…have a total composition of (GalNAc) 16 (GlcNAc) 4 (Gal) 15 (Glc) 6 (NeuAc) 16 Figure 1, and the predictions of the NetOGlyc server [25]. We then selected the eight most likely sites on this basis.…”
Section: Progressing To the O-glycan Zaia Et Al Deduced That The O-mentioning
confidence: 99%
See 2 more Smart Citations
“…have a total composition of (GalNAc) 16 (GlcNAc) 4 (Gal) 15 (Glc) 6 (NeuAc) 16 Figure 1, and the predictions of the NetOGlyc server [25]. We then selected the eight most likely sites on this basis.…”
Section: Progressing To the O-glycan Zaia Et Al Deduced That The O-mentioning
confidence: 99%
“…Thus, one dimensional 1 H NMR of recombinant BSP revealed that the protein is highly flexible along its entire length and exists as an ensemble of A c c e p t e d M a n u s c r i p t 4 completely unstructured conformations in solution [4]. Similarly, two dimensional HSQC NMR of an 15 N labelled recombinant BSP fragment taken from the last 59 amino acids of the protein C-terminus indicated a rapidly flexing random coil structure [5]. Secondary structure prediction programs such as PsiPred [6] also suggest that the unmodified BSP would exist as an essentially unstructured random coil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates 1x10 7 and 2x10 5 viable tumor cells as adequate for intraperitoneal inoculation in Wistar rats, as this amount produces ascites and death within approximately seven days 58,86,87,92 . The fact of tumor dissemination observed in all animals of the experiment can be explained by the formation of new blood vessels [95][96][97] , as it occurs in normal healing process of surgical wounds, and by the loss of cohesion between tumor tissue cells 98 and increased cell motility 99 , resulting from tumor manipulation in rats of group A of laparotomy, and by the flow of gas in pneumoperitoneum in group B.…”
Section: Vol 32 Nºmentioning
confidence: 99%
“…However, breast cancer cells have been shown to express both BSP and OPN, and to upregulate BSP expression in pre-osteoblasts through BMP signalling; and OPN was found localized between cancer cells and bone cells at sites of metastasis (116,117). Moreover, the expression of BSP has been found to correlate with bone metastasis development (118), and OPN expression and serum concentrations have been shown to be poor prognosis markers in breast cancer patients (119,120). As osteopontin is also a mediator of the hematopoietic stem cell niche, directing migration and acting as an adhesion molecule to HSC via 1 integrin (121), it represents a potentially valuable therapeutic target against bone metastases.…”
Section: Attachment Proteins Between Breast Cancer Cells and The Bonementioning
confidence: 99%